6th International conference “Nanobiophysics: fundamental and applied aspects” - Dovbeshko, G. I.; Karachevtsev, V. A.; Berest, V. P.; Kosevich, M. V. (Biophysical Bulletin, 2020)
6th International conference “NANOBIOPHYSICS: Fundamental and Applied Aspects” (NBP-2019) took place on October 1-4, 2019 at the Institute of Physics of the National Academy of Sciences of Ukraine (Kyiv, Ukraine). Previous five conferences, starting from 2009, were organized due to joint efforts of B. Verkin Institute for Low Temperature Physics and Engineering of the NAS of Ukraine and Institute of Physics of the NAS of Ukraine on biennial basis in Kyiv and Kharkiv alternatively.63 leading scientists from 14 countries took part in the conference, Ukraine, Belarus, Italy, France, Latvia, Lithuania, Estonia, Germany, Poland, Check Republics, Canada, Denmark, USA and ARE were represented. 36 scientific lectures, including 17 invited, and 27 poster presentations were made. The goal of the conference was in exchange of information concerning recent achievements in the field of nanobiophysics, aimed at the inspiration of further advancement of basic investigations as well as innovations in the related areas of nanotechnology. Friendly format of the scientific meeting provided the exchange of ideas in such urgent topics as physical properties of biomolecular nanosystems, interactions of biomolecules with nanoparticles and nanostructured surfaces, enhancement of optical processes in biomolecules by nanostructured metal surfaces, formation of nanohybrids of biomolecules with carbon nanostructures, theory and computer modeling of nanoscopic biological systems, applications of bionanomaterials and bionanocomposites. In the framework of the conference special sessions for communications between the participants of the current international projects HORIZON 2020 and NATO Workshop were organized. Book of abstract based on NBP-2019 materials was published.